3D Laparoscopy-Assisted Operation to Adult Intussusceptions During Perioperative Period of Liver Transplantation: Case Report and Literature Review - Gao, Qing; Yuan, Shuo; Li, Yang; Chen, Chao; Liu, Xiaosun; Yu, Jiren (Frontiers in Surgery, 2021)
Adult intussusception during the perioperative period is defined as an extremely rare condition, especially when it emerges within short intervals of laparotomy, which may be explained as an unphysiological peristaltic function of the bowel without any lead points. Accurate diagnosis and therapeutic schedule predict a satisfactory outcome. Here, we introduce the case of a 32-year-old man who had symptoms of abdominal pain, no gas emission, and defecation shortly after liver transplantation. Intussusception was definitely diagnosed by abdominal CT, and then reduction was operated successfully by three-dimensional laparoscopy-assisted operation. There were no other complaints, and no secondary lesions were detected during the postoperative rehabilitation process in the hospital and over a follow-up period of 6 months. Relevant literature has been summarized subsequently. A promising minimally invasive surgery along with minimal secondary trauma was presented by laparoscopy in this rare case, providing the potential remedy for perioperative intussusception in the adult.